A Risk-Based Approach to the COVID-19 Pandemic: The Experience in National Dental Centre Singapore - Tay, John Rong Hao; Ng, Ethan; Ong, Marianne Meng Ann; Sim, Chelsia; Tan, Ken; Seneviratne, Chaminda Jayampath (Frontiers in Medicine, 2020)
The emergence of a highly infectious coronavirus strain, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has led to a major global public health emergency. The increasing number of infected cases and fatalities worldwide forced several countries into lockdown in a bid to control virus transmission. The practice of dentistry is considered high-risk due to the generation of aerosols associated with most dental procedures, and healthcare professionals must take appropriate precautions whilst working in this challenging environment. This review aims to provide an overview on transmission routes and shares a risk-based approach to coronavirus disease 2019 (COVID-19) in a specialty tertiary centre. Risk assessment and mitigation focussed on staff and patient safety, adopting a wide safety margin, and responding dynamically to the level of risk at the workplace. As the severity of the pandemic depends on many still-unknown factors and shows little sign of abating, the routine practice of dentistry will continue to be disrupted in the near future. We describe a colour-coded framework to maximise safety and to minimise disease spread. Areas covered include healthcare team management, personal protective equipment, clinical work, and dental education. Guidelines in each category change with the corresponding severity of the situation, and we believe it will be useful for the safer practice of dentistry in this current climate and can be modified for future similar disease outbreaks